Biochemical and haematological parameters in dogs with Cushing's syndrome - Karić, Ernes; Hodžić, Aida; Zahirović, Amir; Hrković Porobija, Amina; Ohran, Husein (2021)
The exposure of the body to stress, regardless of whether it comes from physical, chemical or emotional stimuli from the environment, causes an inadequate adaptation of the organisms which can contribute to the development of various diseases. Abnormally high blood concentrations of cortisol, known as stress hormone, lead to the development of a hormonal disorder called hyperadrenocorticism or Cushing"s syndrome. In the majority of cases, Cushing"s syndrome is diagnosed when symptoms are apparent, and screening endocrinological test confirms the existence either of increased cortisol production or decreased sensitivity of the hypothalamic-pituitary-adrenal axis to negative glucocorticoid feedback. In our research, we examined a total of 23 male and 7 female dogs that were suspected to have Cushing"s syndrome, based on history and clinical signs. A total of 15 male and 5 female dogs were positive for Cushing"s syndrome (HAC group), whereas the  remaining dogs were used to form non-HAC group. Using the apparatus IDEXX "Vet Test 8008", the following biochemical parameters were determined: glucose, urea, creatinine, phosphorus, calcium, total protein, albumin, globulin, alanine aminotransferase, alkaline phosphatase, bilirubin, cholesterol, and amylase. Regarding haematological parameters, the following parameters were investigated: erythrocytes, leukocytes, platelets, erythrocyte indices (MCV, MCH, MCHC, RDW), white blood cell count, haemoglobin and haematocrit, using "Laser cite vet lab Station" (IDEXX). No significant differences in haematological and biochemical blood parameters were noticed between the HAC and the non-HAC group of dogs. However, dogs suffering from Cushing"s syndrome had a higher value in the number of erythrocytes compared to the control group.
Visoke koncentracije kortizola u krvi, poznatog kao hormon stresa, dovode do razvoja hormonalnog poremećaja koji se naziva hiperadrenokorticizam ili Cushingov sindrom. U većini slučajeva Cushingov sindrom dijagnosticira se kada su simptomi vidljivi, a endokrinološki testovi potvrde ili postojanje povećane proizvodnje kortizola ili snižene osjetljivosti osovine hipotalamus-hipofiza-nadbubrežna žlijezda na inhibirajući učinak glukokortikoida. Naše je istraživanje obuhvatilo ukupno 23 muška i 7 ženskih pasa za koje se na temelju anamneze i kliničkih znakova sumnjalo da imaju Cushingov sindrom. Ukupno 15 muških i 5 ženskih pasa bilo je pozitivno na Cushingov sindrom (HAC skupina), dok su preostali psi grupirani u skupinu pasa bez hiperadrenokorticizma (non-HAC skupina). Pomoću uređaja IDEXX "Vet Test 8008", određeni su sljedeći biokemijski parametri: glukoza, ureja, kreatinin, fosfor, kalcij, ukupni proteini, albumin, globulin, alanin aminotransferaza, alkalna fosfataza, bilirubin, kolesterol i amilaza. Od hematoloških pokazatelja, ispitivani su sljedeći pokazatelji: eritrociti, leukociti, trombociti, hematološki indeksi (MCV, MCH, MCHC, RDW), diferencijalna krvna slika, hemoglobin i hematokrit, korištenjem "Lasercyte Vetlab Station" (IDEXX). Nisu ustanovljene značajne razlike u hematološkim i biokemijskim pokazateljima u krvi između skupine pasa s dijagnosticiranim hiperadrenokorticizmom i bez njega. Međutim, psi oboljeli od Cushingovog sindroma imali su više vrijednosti broja eritrocita u odnosu na kontrolnu grupu, a ustanovljena je i razlika u broju trombocita između skupina koja nije dosegnula statističku značajnost, ali bi na nju trebalo obratiti pozornost.
Bibliografija: 18 jed.
Abstract ; Sažetak.
Keywords: Psi -- Hormonalni poremećaji -- Cushingov sindrom -- Hematološki pokazatelji